2022
DOI: 10.14309/ajg.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Is Associated With Treatment Response in Liver Fat Content by Magnetic Resonance Imaging Independent of Clinically Significant Body Weight Loss in Patients With Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: Exercise training is crucial in the management of nonalcoholic fatty liver disease (NAFLD); however, whether it can achieve clinically meaningful improvement in liver fat is unclear. We investigated the association between exercise training and the achievement of validated thresholds of MRI-measured treatment response. METHODS:Randomized controlled trials in adults with NAFLD were identified through March 2022. Exercise training was compared with no exercise training. The primary outcome was ‡30% relative redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…There are many well-established benefits of regular physical activity and, in particular, exercise training in patients with NAFLD and NASH, as detailed below. 17 Importantly, some of these benefits may be independent of clinically significant weight loss, 42 , 43 including improvements in liver fat (as determined by MRI), cardiovascular health, body composition, cardiorespiratory fitness, and health-related quality of life (HRQOL). Whether weight loss is required for histologic improvement with exercise training is controversial, however, in general, it is accepted that various thresholds of weight loss would be expected to lead to specific histologic changes in patients with NASH (Figure 2 ).…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%
“…There are many well-established benefits of regular physical activity and, in particular, exercise training in patients with NAFLD and NASH, as detailed below. 17 Importantly, some of these benefits may be independent of clinically significant weight loss, 42 , 43 including improvements in liver fat (as determined by MRI), cardiovascular health, body composition, cardiorespiratory fitness, and health-related quality of life (HRQOL). Whether weight loss is required for histologic improvement with exercise training is controversial, however, in general, it is accepted that various thresholds of weight loss would be expected to lead to specific histologic changes in patients with NASH (Figure 2 ).…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%
“…There are many well-established benefits of regular PA and, in particular, exercise training in patients with NAFLD and NASH, including loss of liver fat on imaging, improvement in NASH activity on histology, reversal of endothelial dysfunction, change in body composition, gain in physical fitness, and improvement in health-related quality of life (HRQOL). Importantly, many of these benefits appear independent of clinically significant body weight loss (45,64). Whether weight loss is required for liver fibrosis improvement with exercise training remains unclear; however, in general, it is accepted that at least 7% body weight loss is required to lead to improvement in liver fibrosis across all treatment interventions (18,65,66).…”
Section: Continued Next Pagementioning
confidence: 99%
“…Other modalities of exercise, which have also been shown to reduce liver fat, include resistance training, high-intensity interval training (HIIT), and combined aerobic and resistance training. A recent systematic review and meta-analysis (64) suggests that exercise training achieves rates of clinically significant reduction in MRI-measured liver fat at the threshold, which may be a surrogate for histologic improvement in both NASH activity and liver fibrosis at thresholds adapted from NASH drug trials (82,83). This is important because to date, there is inconsistent evidence that exercise training independently improves liver fibrosis when liver histology is directly examined, despite multiple studies showing histologic NASH activity can be improved, especially in the presence of significant body weight loss (84)(85)(86)(87).…”
Section: Continued Next Pagementioning
confidence: 99%
See 1 more Smart Citation
“…[18] A recent meta-analysis of randomized control trials has also shown that the WHO-recommended dose of PA, compared to a lower dose, is associated with a pooled 3-fold greater odds of ≥ 30% reduction in MRI-measured hepatic steatosis. [19] However, PA alone is unlikely to lead to weight loss without concomitant dietary calorie reduction. And, without significant weight loss, PA does not appear to improve steatohepatitis or fibrosis.…”
Section: Physical Activitymentioning
confidence: 99%